KEANEKARAGAMAN JENIS HIJAUAN SEBAGAI SUMBER PAKAN TERNAK PADA BERBAGAI ZONA AGROEKOLOGI DI KABUPATEN BANTUL DAERAH ISTIMEWA YOGYAKARTA: FORAGE SPECIES DIVERSITY AS A SOURCE OF ANIMAL FEED IN VARIOUS AGROECOLOGICAL ZONES IN BANTUL DISTRICT SPECIAL REGION OF YOGYAKARTA - Widiastuti, Lusia Komala; Kusuma Adhianto; Bayu Andri Atmoko (Tropical Animal Science, 2025)
Goats are one of the small ruminants that contribute significantly to the smallholder livestock system and play a role in increasing the income of rural communities in Indonesia. Forage availability as the main component of goat feed usually depends on landscape conditions and different agroecological zones. Bantul Regency, Special Region of Yogyakarta, has three different agroecological zones: hilly areas, lowland, and coastal areas. This study aims to determine the diversity of forage in various agroecological zones in Bantul Regency, Yogyakarta Special Region as a basis for making policies for developing livestock populations based on the potential of available forage. The research was conducted using a survey method by observing and inventorying the environment around the farmer's residence and interviewing goat farmers in the agroecological zones of coastal areas, lowland, and hilly areas. The results showed that each agroecological zone has a distinctive type of forage, depending on factors such as land slope, soil type, and season. The lowland zone showed the highest forage diversity compared to other zones. The availability of varied forage as a source of animal feed can affect the productivity of goats, which is an important component of the smallholder farming system in Bantul Regency. Keywords: Forage, Goats, Agroecological zones